PENERAPAN MODEL PEMBELAJARAN COOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELASIII SD NEGERI 016PANDAN AIR KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Syarifudin Sukri; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research at performs since its low usufruct IPS'S studying III. class student SDN 016 Pandan Air that haven't reached KKM (Minimum thoroughness criterion) one that is established which is 65with average brazes 61. This appears from peneletian's startup data of 20 students which reach points according to KKM as much 8 students (40%), meanwhile student that haven't reached KKM'S point as much 12 students (60%). Base about problem research do that action brazes with learnings model implement kooperatif STAD'S type(Student Teams Achiviement division) one that intent to increase IPS'S studying result III. class student SDN 016 School Year Water Screw Pines 2014 / 2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Kooperatif's Learning STAD'S Type(Student Teams Achiviement division ), therefore gets to increase IPS'S studying result III. class student SDN 016 Pandan AIr on Merchant activity material at environmentally home and schooled. It can atsee of studying result gotten by student on base score which is with thoroughness percentage 40%, with average 61, worked up on i. cycle with thoroughness percentage 60% by average 65. Worked up again on cycle II.which is with thoroughness percentage 95% by average 80,25. Learned yielding step-up student gets to be seen from step-up percentage of basic score goes to i. UH on first cycle which is 6,55% and of basic score goes to UH II. on second cycle which is 31,55%. Activity step-up learns first cycle with percentage average 84,7% worked up as 95,8% on second cycle. Student activity on first cycle with percentage average 66,66% worked up as 89,58% on second cycle. Of acquired data as above as gets to be known that pass through learning model Implement kooperatif STAD'S type(Student Teams Achiviement division ), can increase IPS'S studying result III. class student SDN 016 Pandan air.Key word: Kooperatif is STAD'S Type, IPS'S Learned result